A review of corporate governance codes and best practices in Nigeria (2015)
Nigeria is lacking behind in terms of development of its corporate governance, codes, policies and enabling laws, this is in contrast to the United Kingdom's regular review and updated corporate governance codes, principles and Best Practices. The UK is continuously reviewing and updating its corporate governance codes and policies. This paper examines the development of corporate governance mechanisms in the UK and Nigeria and further seeks to advocate for a review and update of Nigeria's corporate governance standards to meet global best practices.